Student leadership in Chinese higher education student union: the role of organizational climate and student engagement - Lei Hua; Aida Hanim A. Hamid; Bity Salwana Alias (Institute of Advanced Engineering and Science, 2026)
Student leadership (SL) is a key driver for personal growth, organizational effectiveness, and campus governance. However, in China, less attention has been paid to the development of SL, especially within student unions, which play a central role in governance and representation. Therefore, this research explores the effect of organizational climate (OC) and student engagement (SE) on SL in college student unions and examines the moderating effect of SE. A quantitative survey was conducted, targeting 17,200 student union members in Shanxi Province, China. Data was collected from 500 respondents using online questionnaires through a convenience sampling technique. The direct effect and moderating effect were analyzed by partial least squares-structural equation modeling (PLS-SEM), which was chosen due to its suitability for analyzing complex models. The findings revealed that both OC and SE have a positive effect on SL. Moreover, SE significantly moderates the relationship between OC and SL. This research advances social cognitive theory in the Chinese higher education context. It enhances the understanding of how college climate and individual factors interact to shape SL. Practically, it suggests the importance of fostering a supportive OC and stimulating SE in SL development.